INTERAKSI SOSIAL PADA MEDIA INSTAGRAM OLEH KOMUNITAS ORIFLAME DI KECAMATAN KUTA, KABUPATEN BADUNG - Paramita, Putu Nadia; Punia, I Nengah; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2024)
This research focuses on social interaction on Instagram media by the Oriflame community in Kuta District, Badung Regency. The aim of this research is to explain and analyze sociologically related to social interaction on Instagram media by the Oriflame community in Kuta District, Badung Regency, explain the factors that encourage and inhibit social interaction on Instagram media features, and explain the impact of using Instagram media as a social interaction media in among the Oriflame community. The method used in this research is a qualitative method using the snowball technique. The theory chosen as a scalpel in analyzing this research is the symbolic interaction theory of Herbert Blummer. The results of this research show that the social interaction of the Oriflame community on Instagram is very dependent on interesting and persuasive content, aesthetic value and attractive visuals so as to display products in a creative way and build an authentic product image and attract consumer interest, in other words branding. The driving factors for the community in working on the Oriflame online business are the same goals and interests among members, a supportive Oriflame community environment and technological developments that make it easier to sell Oriflame products, while the inhibiting factor in the Oriflame community working on its online business is a lack of understanding of technology and features. Instagram application, lack of self-confidence and priorities. Then, the impact of using Instagram media as a medium for social interaction among the Oriflame community can be in the form of the economic effectiveness and profit of selling Oriflame products by sellers from online to offline as well as the impact on the lifestyle of communicating by community members on social media and the lifestyle of community members on social media.